2019
DOI: 10.1186/s40425-019-0645-6
|View full text |Cite
|
Sign up to set email alerts
|

Delayed immune-related events (DIRE) after discontinuation of immunotherapy: diagnostic hazard of autoimmunity at a distance

Abstract: Background The risk of delayed autoimmunity occurring months or years after discontinuation of immunotherapy is frequently asserted in the literature. However, specific cases were rarely described until 2018, when a wave of reports surfaced. With expanding I-O indications in the adjuvant/neoadjuvant curative setting, growing numbers of patients will receive limited courses of immunotherapy before entering routine surveillance. In this context, under-recognition of DIRE could pose a growing clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
138
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(146 citation statements)
references
References 94 publications
(39 reference statements)
4
138
1
3
Order By: Relevance
“…In a recent poster presentation of six patients with persistent irAEs requiring immunosuppression 6 months after ICI cessation, two had arthritis, and one each had hepatitis, colitis, dermatitis and neuropathy 22. Delayed initial presentation of irAEs, with symptoms starting even after ICI cessation, is a related concept that is being increasingly recognised 23. Further prospective cohort studies are needed to determine which irAEs besides IA are likely to persist or present after ICI cessation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent poster presentation of six patients with persistent irAEs requiring immunosuppression 6 months after ICI cessation, two had arthritis, and one each had hepatitis, colitis, dermatitis and neuropathy 22. Delayed initial presentation of irAEs, with symptoms starting even after ICI cessation, is a related concept that is being increasingly recognised 23. Further prospective cohort studies are needed to determine which irAEs besides IA are likely to persist or present after ICI cessation.…”
Section: Discussionmentioning
confidence: 99%
“…10 11 Nonetheless, delayed or latent irAEs have been reported months or even years after initiating therapy with onset extending beyond treatment discontinuation. 12 In clinical trials, the analysis of ICI safety in terms of irAEs is generally reported as incidence proportions. Incidence proportion is typically calculated by crude rates, that is, the ratio of the number of patients who developed the specific adverse event at any point in time to the total number of patients in the cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, edoxaban did not cause DAH in our case. There were 2 cases in which lung injury as an irAE had occurred 6 and 8 months after stopping ICIs [12]. These 2 cases do not contradict our finding that DAH continued for more than 10 weeks after discontinuation of durvalumab.…”
Section: Discussionmentioning
confidence: 43%